2019
DOI: 10.1016/j.celrep.2019.10.113
|View full text |Cite
|
Sign up to set email alerts
|

A Genome-wide CRISPR Screen Identifies ZCCHC14 as a Host Factor Required for Hepatitis B Surface Antigen Production

Abstract: Highlights d Genome-wide CRISPR screen identifies host factors regulating HBsAg expression d ZCCHC14 and TENT4A/B stabilize HBsAg expression through RNA tailing d ZCCHC14 forms a complex with TENT4B and the HBV PRE d RG7834 inhibits the enzymatic activity of TENT4A/B within the ZCCHC14-HBV PRE complex

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 51 publications
2
36
0
Order By: Relevance
“…Their cellular activities include stabilization of mRNAs for translation as well as specifying different RNA species for turnover by the exosome complex (Lubas et al, 2011; Vanácová et al, 2005; Warkocki et al, 2018). Recently, ZCCHC14 has been shown to interact with PAPD5 and PAPD7 to support HBV infection (Hyrina et al, 2019) and consistent with that we observed strong reduction of HBV RNA levels in ZCCHC14 KO cells (Figure S8A).…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…Their cellular activities include stabilization of mRNAs for translation as well as specifying different RNA species for turnover by the exosome complex (Lubas et al, 2011; Vanácová et al, 2005; Warkocki et al, 2018). Recently, ZCCHC14 has been shown to interact with PAPD5 and PAPD7 to support HBV infection (Hyrina et al, 2019) and consistent with that we observed strong reduction of HBV RNA levels in ZCCHC14 KO cells (Figure S8A).…”
Section: Resultssupporting
confidence: 92%
“…Lastly, a comparison with results from a CRISPR screen for hepatitis B virus (HBV), a DNA virus replicating through reverse transcription, surprisingly highlighted ZCCHC14 as a shared host dependency factor between HAV and HBV (Figure S1D) (Hyrina et al, 2019). Together, these data illustrate that the host factor requirements for HAV are largely unique compared to other picornaviruses but reveal an unexpected commonality between HAV and HBV infection.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to cancer, CRISPR screens have driven target prioritization for diseases as diverse as Alzheimer’s disease [ 70 ], Huntington’s disease [ 71 ], Type II diabetes [ 72 ], mitochondrial disorders [ 73 ], and ciliopathies [ 74 ]. Of note, many candidates for host-directed therapy have been identified based on independent genome-wide CRISPR screens for the host-dependency or restriction factors of a diverse array of clinically-relevant pathogens [ 75 ], such as HCMV [ 76 ], DENV [ 77 , 78 ]), Enteroviruses [ 79 ], IAV [ 80 , 81 ], HBV [ 82 ], HIV [ 83 ], Norovirus [ 84 , 85 ], SARS-CoV-2, WNV [ 86 , 87 ]), Zika [ 78 , 88 ], Legionella [ 89 ], Salmonella [ 90 ], and Mycobacteria. Application of CRISPR screens for target discovery is primarily bottlenecked by the optimization of relevant assay models.…”
Section: Crispr-based Technologiesmentioning
confidence: 99%